Review of novel energetic polymers and binders – high energy propellant ingredients for the new space race - Tianze Cheng (Designed Monomers and Polymers, 2019)
Current solid rocket propellant formulations still employ traditional ingredients utilized since the 1960s, such as hydroxyl terminated polybutadiene (HTPB). Recent advances in energetic polymer see many binders capable of providing higher specific impulse and burn rates over HTPB. As shown by calculations, even slight increases in specific impulse can drastically increase the maximum payload of a launch system. Therefore, replacing HTPB with energetic binders could provide heavy space missions the needed extra boost. Energetic binders could also be paired with chlorine-free energetic oxidizers to synergistically provide a specific impulse exceedingly higher than the current formulation while reducing pollution. A comprehensive evaluation of the synthesis, mechanical properties, and performance of various trending and overlooked energetic polymers is described. Several outstanding candidates show promising properties to replace HTPB.